The Jamie and Angus stories - Fine, Anne.; Dale, Penny (Cambridge, MA : Candlewick Press, 2002)
Six stories about Angus, a toy bull, and Jamie, the boy who owns him.
Dry clean only -- Uncle Edward teaches Angus to jump -- Flora's wedding -- Tell me the story -- Strawberry creams -- The perfect day.
Horn Book Starred.
Publisher's Weekly.
School Library Journal.
5.5.
5.5
K-3
Keywords: Bulls -- Fiction; Toys -- Fiction; Bulls -- Fiction; Toys -- Fiction